Characterization of aluminium oxide composites - Pathak, Sunil; Dhakar, Balmukund (Centre for Advanced Research on Energy (CARe), 2019)
Three alumina-based composites were fabricated by die compaction followed by sintering. The porous microstructure was analyzed by SEM (Scanning Electron Microscopy) and EDS (Energy Dispersive X-Ray). In order to know the variation in surface roughness parameters (Ra, Rz, Rmax) of alumina composites the surface roughness of the samples was measured using a three-dimensional laser surface roughness analyzer. The microhardness values of the composites were evaluated using Vickers microhardness tester.